The devil's rejects - Zombie, Rob, 1966-; Ohoven, Michael; Haig, Sid, 1939-; Moseley, Bill.; Zombie, Sheri Moon, 1970-; Foree, Ken, 1941-; McGrory, Matthew; Parmet, Philip; Bates, Tyler; Lions Gate Films; Cinerenta (Firm); Cinelamda (Firm); et al. (Santa Monica, CA : Lions Gate Home Entertainment, 2005)
The Texas State Police are set to make a full-scale attack against the murderous Firefly family residence for the thousand plus murders and several disappearances over the past couple of years. But three of the family members escape, including Otis, Baby Firefly and Baby's father Captain Spaulding. The evil trio go on a road trip, leaving dozens of mangled bodies in their wake. Evading a massive Texas Rangers dragnet as well as a group of equally murderous bounty hunters led by Ken Dwyer who's obsessed with finding the deadly killers. The surviving Firefly clan gather at a run-down amusement park owned by Captain Spaulding's half-brother. Charlie offers them shelter and a new base of operations for their killing spree.
Disc 1. Feature film ; special features. -- Disc 2. 30 days in Hell : the making of The devil's rejects. (144 min.).
Originally produced as a motion picture in 2005.
Special features: Blooper reel; Morris Green Show; 2 Spaulding commercials; Otis home movie; deleted scenes; 2 music videos; stills gallery; 2 feature-length commentaries.
Director of photography, Phil Parmet ; editor, Glenn Garland ; music, Tyler Bates ; costume designer, Yasmine Abraham ; production designer, Anthony Tremblay ; visual effects supervisor, Robert Kurtzman.
Sid Haig, Bill Moseley, Sheri Moon Zombie, Ken Foree, Matthew McGrory, Leslie Easterbrook, Geoffrey Lewis, Pricilla Barnes, William Forsythe.
MPAA rating: Unrated; for sadistic violence, strong sexual content, language and drug use.
DVD, NTSC, region 1, widescreen presentation; Dolby Digital.
Keywords: Murder -- Texas -- Drama; Murder -- Investigation -- Texas -- Drama; Families -- Texas -- Drama; Horror films; Slasher films; Fiction films; Feature films; Feature films -- United States; Feature films -- Germany; Video recordings for the hearing impaired